STRATEGI PENANAMAN IDEOLOGI PANCASILA SEBAGAI SOLUSI TERKIKISNYA NASIONALISME MELALUI PENGEMBANGAN MODEL PEMBELAJARAN BERORIENTASI KOMPETENSI PENDIDIKAN KEWARGANEGARAAN PERGURUAN TINGGI - Winarno _; Sri Haryati; Moh. Muhtarom (Universitas Gadjah Mada, 2013)
This paper explained the potential threat among the university student, internal and external threat. Internal threat showed of skepticism on Pancasila ideology which triggered the disappointment on the state, the external threat was the other side efforts to socialized other ideology with various ways to decreased nationalism. The qualitative and quantitative data showed there area strong supports on Pancasila ideology among the majority of university student. The personality establishment course at the university’s rule was supporting the ideology establishment effort; however there were some problems which related to its learning, as the monotone lecturer learning model and grading instrument which was not appropriate with the measured competence. The developed model strategy was a contra ideology with unique steps.Keywords: Nationalism, Pancasila Ideology, Learning Model, Citizenship Education, and University.